Reports of international arbitral awards = Recueil des sentences arbitrales : vol 1 - United Nations; International Court of Justice. Registry; United Nations. Legal Department; United Nations. Office of Legal Affairs; United Nations. Codification Division (New York : United Nations)
Includes the decisions of the Permanent Court of Arbitration.
Also issued online.
English and French.
Vols. 1-3 prepared by the International Court of Justice Registry; v. 4-5 by the Legal Dept., United Nations Secretariat; v. 6-7 by the Office of Legal Affairs of the Secretariat of the U.N.; v. 8-20 by the Codification Division, Office of Legal Affairs of the Secretariat of the U.N.
Latest issue consulted: Vol. 26, published in 2009.
SERBIB/SERLOC merged record
Keywords: Arbitration (International law) -- Cases; International law -- Sources; Arbitration (International law); International law -- Sources; Internationale arbitrage; ARBITRAL AWARDS; Arbitration (International law); International law; Sources; Trials, litigation, etc